Harmful algal blooms and their effects in coastal seas of Northern Europe - Karlson, Bengt; Andersen, Per; Arneborg, Lars; Cembella, Allan; Eikrem, Wenche; John, Uwe; West, Jennifer Joy; Klemm, Kerstin; Kobos, Justyna; Lehtinen, Sirpa; Lundholm, Nina; Mazur-Marzec, Hanna; et al. (Harmful Algae, 2021)
Highlights • Fish mortalities due to harmful algae cause substantial economic and social costs for the fish farming industry in the northeastern Atlantic, North Sea and adjacent European waters • Toxin syndromes associated with Diarrhetic Shellfish Toxins and Paralytic Shellfish Toxins and their regulation have the most profound effect on the bivalve aquaculture industry in the northeastern Atlantic region • Cyanobacteria and cyanotoxins are mainly problems in brackish water areas, particularly in the Baltic Sea • Emerging threats to the shellfish and finfish industries include the known presence of the phycotoxins azaspiracids and goniodomins • The IOC-ICES-PICESHAEDAT contains time-series baseline information on harmful algal events in Europe Harmful algal blooms (HAB) are recurrent phenomena in northern Europe along the coasts of the Baltic Sea, Kattegat-Skagerrak, eastern North Sea, Norwegian Sea and the Barents Sea. These HABs have caused occasional massive losses for the aquaculture industry and have chronically affected socioeconomic interests in several ways. This status review gives an overview of historical HAB events and summarises reports to the Harmful Algae Event Database from 1986 to the end of year 2019 and observations made in long term monitoring programmes of potentially harmful phytoplankton and of phycotoxins in bivalve shellfish. Major HAB taxa causing fish mortalities in the region include blooms of the prymnesiophyte Chrysochromulina leadbeateri in northern Norway in 1991 and 2019, resulting in huge economic losses for fish farmers. A bloom of the prymesiophyte Prymnesium polylepis (syn. Chrysochromulina polylepis) in the Kattegat-Skagerrak in 1988 was ecosystem disruptive. Blooms of the prymnesiophyte Phaeocystis spp. have caused accumulations of foam on beaches in the southwestern North Sea and Wadden Sea coasts and shellfish mortality has been linked to their occurrence. Mortality of shellfish linked to HAB events has been observed in estuarine waters associated with influx of water ...